КӨКШЕТАУ ӨҢІРІ КӨЛДЕРІ СУЫНЫҢ САПАСЫН ИНТЕГРАЛДЫҚ КӨРСЕТКІШТЕРМЕН БАҒАЛАҒАН НƏТИЖЕЛЕР (Experimental biology, 2015)
In work the regular analysis is carried out and is determined on seasonal taxonomy specific structure and seasonal dynamics of algoflors of lakes (Kopa, Burabai, Zerenda ) in Kokshetau region. If to give a complex estimation specific structure algosenoz and results of biotesting andcarried out hydrochemical, microbiological researches, is established, that waters of lake Коpа concern to 5 class of a level of pollution; waters of lakes Burabai and Zerenda concern to 3 class of a level of pollution.
Keywords: Kokshetau region